Differences in color between early gastric cancer and cancer-suspected non-cancerous mucosa on linked color imaging - Kanzaki, Hiromitsu; Kawahara, Yoshiro; Satomi, Takuya; Okanoue, Shotaro; Hamada, Kenta; Kono, Yoshiyasu; Iwamuro, Masaya; Kawano, Seiji; Okada, Hiroyuki (Endoscopy International Open, 2023)
Background and study aims Linked color imaging (LCI) can enhance the original color of each area and may useful to detect tumorous lesions during esophagogastroduodenoscopy. However, LCI may also enhance cancer-suspected non-cancerous regional color change. We conducted a retrospective image analysis to investigate the color characteristics of early gastric cancer (EGC) and cancer-suspected non-cancerous mucosa (CSM) in LCI.Methods LCI images of both EGC and CSM were retrospectively collected from the database of the institution. Fifteen endoscopists individually judged each image as EGC or CSM. The color difference between the inside and outside of the lesions was measured by CIE-Lab analysis in both groups and compared.Results A total of 245 LCI images of EGC (169) and CSM (76) were extracted and randomly lined for image collection. The test by the endoscopists showed accuracy, sensitivity, and specificity of 64.0 %, 63.7 %, and 64.0 %, respectively. Although the color difference between EGC and CSM was almost the same (12.5 vs. 12.9, not significant), each parameter of ΔL (bright: –0.3 vs. –2.7, P  < 0.001), Δa (Reddish: 7.2 vs. 9.6, P = 0.004), and Δb (Yellowish: 6.4 vs. 3.8, P  < 0.001) was significantly different in the groups. The color feature of both positive ΔL and Δb to EGC showed accuracy, sensitivity, and specificity of 54.7 %, 39.6 %, 88.2%, respectively.Conclusions The total color difference was almost the same between EGC and CSM; however, their color tones were different on linked color imaging. Although the color characteristics of EGC had high specificity, they also had low sensitivity.